Numerical and experimental investigation of an airfoil design for a Martian micro rotorcraft. Issue 3 (September 2018) - Désert, T; Moschetta, JM; Bézard, H
The present paper aims at investigating the impact of an airfoil design on the propulsion system for a Martian rotary wing micro air vehicle. The main challenge for flying on Mars is the atmosphere's density and speed of sound that are significantly lower than on Earth. It leads to compressible ultra-low Reynolds number (R e c < 10 4 ) flows for a coaxial rotorcraft with a 30 cm diameter . Since those flows are unknown in the biosphere, numerical tools have not been validated yet. Therefore, the test section from a known depressurized experiment is simulated in 3D for solver assessment. XFoil, a program for the analysis of subsonic airfoil, is also evaluated in the Martian flow conditions for evaluating its ability to be used in an optimization process. Based on the XFoil's performance evaluations, both the camber line and thickness distribution are optimized in 2D incompressible and compressible flows. Optimal shape is a highly cambered airfoil shifting the boundary layer separation downstream. For optimization assessment, airfoils from each optimization step are numerically evaluated with the validated solver showing that small variations in the airfoil design has little impact on the 2D aerodynamic performance. A compressible optimal airfoil is also proven to be more aerodynamically effective than the experimentally effective airfoils from literature. Finally, the impact of airfoil shapes on the 3D rotor performance is evaluated with a depressurized experimental campaign recreating the Martian atmosphere in terms of kinematic viscosity. The impact of gas composition is also assessed in subsonic flows.